Impact of No Tillage and Low Emission N Fertilization on Durum Wheat Sustainability, Profitability and Quality - Michele Andrea De Santis; Luigia Giuzio; Damiana Tozzi; Mario Soccio; Zina Flagella (Agronomy)
Mitigation practices for cereal systems, including conservation agriculture and low emission fertilization, are required to face global challenges of food security and climate change. The combination of these climate-smart approaches was investigated for durum wheat in a dry region of the Mediterranean basin in two crop seasons. The experimental design consisted in two different genotypes, Marco Aurelio (high protein content) and Saragolla (higher adaptability), subjected to no tillage (NT) vs. conventional tillage (CT) and to two fertilization strategies (standard vs. low emission plus an unfertilized control). Different environmental and economic sustainability parameters as well as two different technological and nutritional quality traits were evaluated. Saragolla showed a better environmental adaptability and a higher nitrogen use efficiency, evaluated as partial nutrient balance (+27%), and was associated with a lower protein content (14.5% vs. 15.6%). NT was associated with an improvement in yield (+15%) and quality, i.e., micronutrients (Fe, Zn) and antioxidant capacity (+15%), in the drier crop year. Low emission fertilization did not reduce crop performance and its combination with NT showed a higher economic net return. The combination of the two mitigation practices improved not only environmental and economic sustainability but also the health quality of durum wheat under water limited conditions.